Proposed Strategy for Broadband Business Using Fiber-To- The-Home (FTTH) Technology for PT Telekomunikasi Indonesia - Ferdinansari, Chindia; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2014)
Abstract— Telecommunication industry in Indonesia is continuously growing with highly competitive market and increasing bandwidth requirement caused by high bandwidth application content, carrying voice, data (Internet) and also IPTV. Fiber-To-The-Home (FTTH) is one of advanced technology in Broadband that use fiber optic until customer home and ready to serve high-speed bandwidth. PT.Telekomunikasi Indonesia (Telkom) implement FTTH by replacing DSL (Digital Subscriber Line) or Copper Cable gradually at some selected area in Indonesia. Telkom provide triple play service that bundled phone, Internet (Speedy) and IPTV (UseeTV) as a bundled service, which is called IndiHome. Business Issue for this study is low subscription rate of Fixed Broadband (FBB) Service at FTTH implemented area including low penetration service that lead to big idle capacity, compared with Global Benchmark data. Objective of this study is to improve Telkom FBB service using FTTH technology that lead to increasing of market penetration by knowing the cause of low subscription rate of Telkom FBB service using FTTH technology and know the important aspect from customer of the service to be improved. The root causes are lack of marketing activities concerning in FTTH technology differentiation, communication about competitive advantage of IndiHome, lack of churn prevention program, customer touch points are not maximize and fully optimize as an effective sales channel and also as a one stop information and lack of activities that give experience and educate the customer about high bandwidth provided by FTTH as a stimulation. Business solution for defined business issue emphasize on marketing activities improvement in order to create awareness of customer about the product/service regarding the technology, advantage and service differentiation. Keywords: Internet, Broadband, FTTH, Triple-Play Service, IndiHome